Management of food legume pod borer and aphids through intercropping in Morocco - Boulamtat, Rachid; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2023)
Food legumes (faba bean, field pea, lentil, and chickpea) productivity and production are affected by aphids and pod borers in rainfed and irrigated production systems in CWANA region. Farmers are practicing several cropping systems that can play both positive and negative roles on insect pests. Intercropping is one of the systems that plays a major role in contributing to pest management practices in many countries. In Morocco, coriander (Coriandrum sativum L.) is produced by farmers as sole and intercropping system. The role of coriander intercropping with chickpea to manage pod borer of chickpea and food legume aphids was not explored under Moroccan cropping systems.